The concept of reliable information on the global network in times of crisis - Kazimi, Parviz Firudın Oqlu; Guliyeva, Nigar Aliagha Gizi (Technium Social Sciences Journal, 2022)
The repertoire of information resources, the acquisition of resources in the process of organizing information services and implementing information policy, democratic principles are an important requirement of a modern cultural society. Library and information institutions are active participants in the information process. In this process, the question of the reliability of information is more important than ever. Our sociological surveys and analysis of the results, conducted with the aim of forming students' habits of searching for information, show that the solution to the problem is not expressed in a "meaningful response." If the lack of a mass reading habit among young people, or rather its lack of formation, leads to social problems, then, on the other hand, we live in a time when the need for reading among young people is growing rapidly, and it cannot be argued that young people read less. Therefore, to determine the social architecture of information processes, it is necessary to ensure the development of a specific model of information reliability. It is important to provide young consumers of information who are prone to ready-made answers with methodological knowledge about the reliability of information. 1-Documents whose distribution in the global environment is limited for various reasons. 2- Current or regulatory laws, ordinances, and other official documents that restrict the dissemination and publication of information in the state or regions. 3 - Characteristics of the specialist's belonging to a particular society, state or group, which determine the national, religious, social and cultural environment. 4- Multinationality, multi-confessionalism, reliability of information in multilingual geography. 5 - Reflects the personal and individual parameters of a specialist. This includes his level of education, gender, vocational education, age, nationality, religious preferences, as well as practical skills. 6 - Norms formed by various institutions. The listed cases consist of a general analysis. There is no doubt that persons and organizations involved in the dissemination of information are representatives of different subjectivity, and in most cases, personal thoughts and views are expressed in the presented information product. Interesting results were found in a questionnaire that allows young people to choose from the following nine responses to the question of how to determine the validity of information when searching for information. At the stage when our habits of information search are formed, let's pay attention to the situation when there is a conflict of interest. It is accepted in the academic community that it is impossible to quote Wikipedia and YouTube materials when writing scientific articles and speaking at scientific conferences, as this undermines the scientific character and prestige of the article. Although I did not know where these "norms" were written, I was treated appropriately, and my protest against the illogicality of this approach did not change anything. I want to draw your attention to the fact that the vast majority of young people are 90% satisfied with their needs for information (especially factual information) from Wikipedia. As a result of our surveys, young people not only considered the information they received from Wikipedia to be reliable, but were even ready to argue about it with teachers. It should be recognized that the "invisibility" of Wikipedia in the academic community is not accidental, and there is a consensus among researchers. However, it is wrong not to speak or discuss Wikipedia and various other "information resources" that create a wide information environment around us. This refers to the reconciliation of specialists with the rapid spread of unreliable information products. Errors in the belonging of historical materials, ethnographic, applied and fine arts, etymological interpretation and linguistics can be in some cases deliberate, and sometimes out of ignorance. Leaving aside serious research by historians, a number of Wikipedia articles promoting "cosmopolitan" interpretations require prompt responses, otherwise we will resign ourselves to these facts and allow students to gain harmful knowledge from these resources.